The Tenth Grade Students’ Perception towards Learning English in Online Classes at Puspita Senior High School - Rizky, Rizky Lutfi Ahmadi; Magdad Hatim (English Education:Journal of English Teaching and Research, 2022)
This study aims to find out the perception of learners about learning English online classes at Puspita Senior High School. The subject of this study consists of two classes namely X IPA 1 consisting of 30 learners and X IPS 1 consisting of 31 learners. This research method uses descriptive qualitative through three data collection techniques, namely 1) observations made during the learning process; 2) questionnaire, given to students to find out the perception of students who have previously been validated by experts; and 3) Interviews, conducted to teachers and principals who are used to support other data. From the data obtained then data analysis was conducted consisting of 1) reduction of data that chooses the core of the data obtained through observation, questionnaire, and interview. After that 2) the presentation of data presented through tables, graphs, and brief descriptions. Then 3) drawing conclusions that answer the formulation of the problem. Based on the results of the study it can be concluded that the majority of learners have a positive perception of online classes. But there are still some learners who experience frustration when online classes are implemented. Keywords:Analysis, learning difficulties, student perception